The potential of genomics in plant systematics. Issue 5 (30th December 2018) - Soltis, Douglas E.; Gitzendanner, Matthew A.; Stull, Gregory; Chester, Michael; Chanderbali, Andre; Chamala, Srikar; Jordon-Thaden, Ingrid; Soltis, Pamela S.; Schnable, Patrick S.; Barbazuk, W. Brad
Abstract: Next‐generation sequencing (NGS) has revolutionized molecular systematics as well as population and conservation genetics. It is now possible to obtain enormous amounts of gene sequence data from any species in a short time at low cost. More technological advances are on the horizon, ensuring that this trend will continue throughout the coming decade. These rapid advances provide unprecedented opportunities in systematics; they also pose new challenges, requiring that the next generation of systematists be well‐versed in new skill sets (e.g., bioinformatics). As examples of the potential of NGS, it is now possible to develop genetic resources for any plant system that poses intriguing evolutionary questions. During the next decade many new "evolutionary model systems" will become available as systematists rapidly develop the necessary genetic/genomic frameworks for many previously unstudied plants. Phylogenetic reconstruction will be conducted at an unprecedented pace at both deep and fine scales with datasets of numerous taxa and genes—this includes rapid progress on assembling a more comprehensive Tree of Life for green plants. For example, complete plastid genome sequencing is now routinely facilitating analyses of hundreds of taxa at deep levels, as well as enabling complete plastid genome phylogeographic analyses at the population level. Gene capture methods hold enormous promise for the rapid and inexpensive analyses of complete plastid genomes, as well as studies of hundreds of selected (targeted) nuclear loci. NGS has also had a big impact on population genetics, initially by dramatically simplifying microsatellite marker development, but more recently by opening new possibilities through various genotyping‐by‐sequencing (GBS) approaches that have great potential to expand on the types of questions that can be addressed at the population level. Transcriptome sequencing has enabled the construction of large datasets of nuclear genes while also providing a wealth of plastid and mitochondrial genes. NGS has also facilitated probe development for studies of chromosomes using FISH (fluorescence in situ hybridization). NGS is also making the rapid sequencing of complete nuclear genomes routine, thus transforming our field and opening up new avenues of systematic endeavor in comparative genomics. However, even as sequencing costs drop and technological advances make complete nuclear genome sequencing more commonplace, genome assembly will remain a major challenge.